2000
DOI: 10.1086/308747
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Angle Spectrometric Coronagraph Measurements of the Energetics of Coronal Mass Ejections

Abstract: We examine the energetics of coronal mass ejections (CMEs) with data from the large-angle spectrometric coronagraphs (LASCO) on SOHO. The LASCO observations provide fairly direct measurements of the mass, velocity, and dimensions of CMEs. Using these basic measurements, we determine the potential and kinetic energies and their evolution for several CMEs that exhibit Ñux-rope morphologies. Assuming Ñux conservation, we use observations of the magnetic Ñux in a variety of magnetic clouds near the Earth to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
247
4
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(275 citation statements)
references
References 30 publications
23
247
4
1
Order By: Relevance
“…Hence the parameters derived from the plasma emission model of the prominence/type IV burst of 1990 September 14 are comparable to Hα analyses of large erupting prominences. They are also comparable to values reported for CMEs by the coronagraphs aboard Skylab (Rust et al 1980), Solwind (Webb et al 1996), SMM (Hundhausen et al 1994) and SoHO (Lyons et al 1999;Vourlidas et al 2000), but are an order of magnitude above estimates from X-ray analyses (Hudson et al 1996;Gopalswamy et al 1997). The kinetic energy is near the upper limits of CME values.…”
Section: Estimate Of the Mass And Energetics Of The Ejected Plasma Blsupporting
confidence: 85%
“…Hence the parameters derived from the plasma emission model of the prominence/type IV burst of 1990 September 14 are comparable to Hα analyses of large erupting prominences. They are also comparable to values reported for CMEs by the coronagraphs aboard Skylab (Rust et al 1980), Solwind (Webb et al 1996), SMM (Hundhausen et al 1994) and SoHO (Lyons et al 1999;Vourlidas et al 2000), but are an order of magnitude above estimates from X-ray analyses (Hudson et al 1996;Gopalswamy et al 1997). The kinetic energy is near the upper limits of CME values.…”
Section: Estimate Of the Mass And Energetics Of The Ejected Plasma Blsupporting
confidence: 85%
“…However, a CME is a three dimensional structure with a significant depth along the line-of-sight. It has been reported earlier that such an assumption leads to underestimation of the CME mass by 15% (Vourlidas et al, 2000). We made several independent mass measurements for this event and found that the values are within 20% of the measured ones.…”
Section: Momentum Energy Exchange and Nature Of The Collisionsupporting
confidence: 68%
“…Assuming that the CME observed in white-light is due to Thomson scattered photospheric light from the electrons in the CME (Minnaert, 1930;Billings, 1966;Howard and Tappin, 2009), the recorded scattered intensity can then be converted into the number of electrons, and hence the mass of a CME can be estimated, assuming a completely ionized corona with a composition of 90% hydrogen and 10% helium. In earlier studies (Munro et al, 1979;Poland et al, 1981;Vourlidas et al, 2000), the mass of a CME was calculated assuming the CME location in the observer's plane of sky. We use the method of Colaninno and Vourlidas (2009) which is based on the Thomson scattering theory, to estimate the true propagation direction and true mass of both CMEs.…”
Section: Momentum Energy Exchange and Nature Of The Collisionmentioning
confidence: 99%
“…The CME in particular contains a great deal of kinetic energy (e.g., Vourlidas et al 2000;Emslie et al 2005) show, for two major flares (the RHESSI flares of SOL2002-04-21T01:51 and SOL2002-07-23T00:35), that the CME kinetic energy is of the same order of magnitude as the radiated energy. In some well-studied cases (e.g., Robbrecht et al 2009) virtually no flare-like emissions can be detected at all.…”
Section: Large-scale Motions and A Mythmentioning
confidence: 99%